Tree Assistance Program For Florida Citrus Greening - Ariel Singerman; Fritz Roka (EDIS)
In September 2014, the USDA Farm Service Agency (FSA) announced additional support for commercial Florida citrus growers to manage greening, in the form of an expansion of the Tree Assistance Program (TAP). The original program assisted growers in the event the loss occurred within a single year due to a natural disaster such as a hurricane. The expanded TAP recognizes citrus greening (Huanglongbing, or HLB). The program provides growers cost-sharing financial assistance to replace trees that meet a mortality criterion within a time period of up to six years. This 4-page fact sheet describes eligibility requirements, how the program works, and how to calculate payments. Written by Ariel Singerman and Fritz Roka, and published by the UF Department of Food and Resource Economics, April 2015.